An accurate closed-form approximate representation for the Hankel function of the second kind. - Gardner, J. (IEEE Transactions on antennas and propagation)
A second-order asymptotic evaluation of the Hankel function is presented and its numerical evaluation for the case of large orders and large arguments is compared with the numerical results obtained using forward recursion. It is shown that the second-order results are very accurate as long as the argument is a few percent larger than the order of the function